Hydrogen degradation of materials and changes in the operating mode of compressor station equipment as factors of increased risks and costs during transportation of hydrogen-containing gas through main gas pipelines - A. G. Ishkov; O. V. Zhdaneev; K. V. Romanov; E. A. Koloshkin; S. Yu. Nastich; V. А. Egorov; A. B. Arabey; A. Yu. Mikhalev; V. A. Lopatkin; А. Г. Ишков; О. В. Жданеев; К. В. Романов; et al. (Международный издательский дом научной периодики "Спейс, 2025)
The problems of changing the operating modes of the main technological equipment of compressor stations (CS) of the existing gas transmission system, as well as the degradation of the mechanical properties of the CS equipment material in the case of transportation of methane-hydrogen mixtures or hydrogen at elevated pressure, are considered. The features of operation of a centrifugal compressor during pipeline transportation of hydrogen-containing mixtures are considered. Due to the peculiarities of the physico-chemical properties of hydrogen, which lead to an increase in the flow rate, an increase in the rotational speed of the compressor rotor is required, which is limited by regulatory requirements. When used with hydrogen-containing mixtures, the risk of embrittlement of the rotor material increases. The results of tests to assess the resistance to hydrogen embrittlement of structural steels of different classes, which are characteristic materials of CS equipment, are presented. The main patterns of changes in strength, ductility, and crack resistance of steels at hydrogen concentrations from 5% to 100% and pressures of 10 MPa have been established. In a hydrogencontaining environment, high-strength steels are softened and strongly embrittled. Рассмотрены проблемы изменения режимов работы основного технологического оборудования компрессорных станций (КС) существующей газотранспортной системы, а также деградации механических свойств материала оборудования КС в случае транспортировки метановодородных смесей или водорода при повышенном давлении. Рассмотрены особенности работы центробежного компрессора при трубопроводной транспортировке водородсодержащих смесей. Вследствие особенностей физико-химических свойств водорода, приводящих к повышению скорости потока, требуется увеличение частоты вращения ротора компрессора, что ограничено нормативными требованиями. При эксплуатации с водородсодержащими смесями повышается риск охрупчивания материала ротора. Представлены результаты испытаний для оценки сопротивляемости ...